The Implementation of English Training in the Marketing of Fishery Products in Cirebon City - Eliyawati, Eliyawati; Kurniawan, Zuki; Indriyani, Devia (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2025)
The marketing of fishery products in Cirebon City continues to encounter challenges in penetrating global markets, primarily due to the limited English communication skills among business actors. This study aims to examine the impact of English language training on the effectiveness of fishery product marketing. A quantitative research approach was employed using a survey method. Data were collected through questionnaires distributed to 100 fishery entrepreneurs who had participated in a three-month English language training program. Data analysis involved descriptive statistics and simple linear regression to determine the relationship between the training and marketing effectiveness. The findings reveal that English language training significantly improved the participants’ communication skills in promoting their products to international markets (p-value < 0.05). Moreover, the use of English-based digital marketing strategies increased from 40% prior to the training to 75% afterward. These results highlight the essential role of English language training in enhancing the global competitiveness of fishery products. The study recommends the implementation of more targeted training programs integrated with digital literacy to support successful international marketing initiatives.